2014
DOI: 10.4238/2014.june.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of geographic and pairwise distances among sheep populations

Abstract: ABSTRACT. This study investigated geographic and pairwise distances among seven Chinese local and four introduced sheep populations via analysis of 26 microsatellite DNA markers. Genetic polymorphism was rich, and the following was discovered: 348 alleles in total were detected, the average allele number was 13.38, the polymorphism information content (PIC) of loci ranged from 0.717 to 0.788, the number of effective alleles ranged from 7.046 to 7.489, and the observed heterozygosity ranged from 0.700 to 0.768 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Microsatellite markers belong to a class of neutral markers, which have rich polymorphism in population and are widely distributed in the genome; therefore they are suitable for genetic diversity analysis. Previous studies indicated that microsatellite markers had been well used to assess genetic diversity and population structure of sheep breeds (Di et al, 2012;Dotsev et al, 2018;Madilindi et al, 2019;Vargas et al, 2018;Laoun et al, 2020;Ullah et al, 2020) and goat breeds (Carvalho et al, 2015;Câmara et al, 2017;E et al, 2019;Liu et al, 2019). Therefore, in this study, a panel of 26 microsatellite markers was employed to evaluate the genetic diversity, population structure and phylogenetic relationship of the nine sheep populations.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers belong to a class of neutral markers, which have rich polymorphism in population and are widely distributed in the genome; therefore they are suitable for genetic diversity analysis. Previous studies indicated that microsatellite markers had been well used to assess genetic diversity and population structure of sheep breeds (Di et al, 2012;Dotsev et al, 2018;Madilindi et al, 2019;Vargas et al, 2018;Laoun et al, 2020;Ullah et al, 2020) and goat breeds (Carvalho et al, 2015;Câmara et al, 2017;E et al, 2019;Liu et al, 2019). Therefore, in this study, a panel of 26 microsatellite markers was employed to evaluate the genetic diversity, population structure and phylogenetic relationship of the nine sheep populations.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve simple sequence repeats were detected in the 21 duck breeds. Nei’s standard genetic distance was estimated using Microsatellite-Toolkit and Dispan 24 . According to the genetic distance matrix (Table 3) and cluster analysis by the unweighted pair-group method with arithmetic means (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The use of microsatellites had a special echo in the selection of sheep and goats to characterize certain breeds and determine their genetic distance. These studies are still relevant today (Liu et al, 2014;Zinovieva et al, 2015). In recent years, more than 50,000 SNPs have been tested to see their association with individual production traits.…”
Section: Genetic Diversity Of Populationsmentioning
confidence: 99%
“…Microsatellite markers could use to analyze genetic diversity in sheep breeds (Gaouar et al, 2012;Liu et al, 2014;Ebrahimi et al, 2017;Xia et al, 2021), goat (Bindu et al, 2012Hussain et al, 2013;Seilsuth et al, 2016;Asroush et al, 2018), and the other domestic animals (Petrovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation